Serotonin 5-HT2C Receptor Activation Suppresses Binge Intake and the Reinforcing and Motivational Properties of High-Fat Food - Price, Amanda E.; Anastasio, Noelle C.; Stutz, Sonja J.; Hommel, Jonathan D.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2018)
Binge eating disorder (BED) is characterized by dysfunctional hedonic food intake and reward-related processes. Activation of the serotonin (5-HT) 5-HT2C receptor (5-HT2CR) suppresses both food intake and reward-related behaviors and is thus poised to regulate BED. This study assessed the effects of 5-HT2CR activation via the selective 5-HT2CR agonist WAY163909 on binge eating-related behaviors in adult male Sprague-Dawley rats. Low doses of WAY163909 (1.0, 2.0 mg/kg) suppressed high fat food (HFF) binge intake, but not standard food non-binge intake. WAY163909 (1.0 mg/kg) also attenuated operant responding for self-administered HFF pellets on fixed and progressive ratio schedules of reinforcement, indicating that 5-HT2CR activation suppresses the reinforcing and motivational properties of HFF, respectively. These findings suggest that activation of the 5-HT2CR may be effective at suppressing binge eating in patients with BED via suppression of the reinforcing and motivational properties of HFF. This work supports future studies targeting the 5-HT2CR in the treatment of BED.